Report of the final meeting of the Agroecological Initiative in Burkina Faso - Orounladji, Boko Michel; Outtara, Songdah Désiré; Sib, Ollo; Fayama, Tionyélé; Sodre, Etienne; Traore, Issouf; Ouattara, Baba; Kiendrebeogo, Timbilfou; Ouedrago, Souleymane; Vall, Eric (2024)
The final meeting of teh CGIAR initiative on Agroecology aimed to present the main results to members of the ALL and other stakeholders in the Bobo-Dioulasso dairy sector, and to discuss prospects. Specifically, this involved : (1) Recall the objectives, activities and results targeted by the AEI; (2) Present and discuss the results obtained by WP, the perceived outcomes and the initial impacts of the Initiative; (3) Assessing stakeholder satisfaction; and (4) Exhibit ALL agroecological innovations and new ageoecological dairy products.